The role and mechanism of TCM in the prevention and treatment of infectious diseases - Zou, Qifei; Chen, Yitong; Qin, Huanxin; Tang, Rui; Han, Taojian; Guo, Ziyi; Zhao, Juanjuan; Xu, Delin (Frontiers in Microbiology, 2023)
The constant presence of infectious diseases poses an everlasting threat to the entire world. In recent years, there has been an increased attention towards the application of traditional Chinese medicine (TCM) in the treatment of emerging infectious diseases, as it has played a significant role. The aim of this article is to provide a concise overview of the roles and mechanisms of TCM in treating infectious diseases. TCM possesses the ability to modulate relevant factors, impede signaling pathways, and inhibit microbial growth, thereby exhibiting potent antiviral, antibacterial, and anti-inflammatory effects that demonstrate remarkable efficacy against viral and bacterial infections. This article concludes that the comprehensive regulatory features of Chinese herbal medicines, with their various components, targets, and pathways, result in synergistic effects. The significance of Chinese herbal medicines in the context of infectious diseases should not be underestimated; however, it is crucial to also acknowledge their underutilization. This paper presents constructive suggestions regarding the challenges and opportunities faced by Chinese medicines. Particularly, it emphasizes the effectiveness and characteristics of Chinese medicines in the treatment of infectious diseases, specifying how these medicines' active substances can be utilized to target infectious diseases. This perspective is advantageous in facilitating researchers' pharmacological studies on Chinese medicines, focusing on the specific points of action. The mechanism of action of Chinese herbal medicines in the treatment of infectious diseases is comprehensively elucidated in this paper, providing compelling evidence for the superior treatment of infectious diseases through Chinese medicine. This information is favorable for advancing the development of TCM and its potential applications in the field of infectious diseases.